VSI Based DSTATCOM for Compensating Nonlinear and Unbalanced Loads - R.REDDY, S; V.PRASAD, P; N.SRINIVAS, G (International Journal of Engineering and Technology, 2018)
This paper presents study of distribution static compensator (D-STATCOM) for compensation of neutral current, source&PCC current harmonic distortion,Â PCC voltage regulation and compensation of unbalanced current waveform for the three phase four wire nonlinear andÂ unbalanced load medium voltage distribution system. The proposed control algorithm is developed based on synchronous reference frame theory with PI controller. The obtained reference current signal from control algorithm is compared in hysteresis band current controller for better switching of D-STATCOM. The performance of system without & with D-STATCOM is also analysed and compared. The proposed control method is implemented on 11/0.4kv medium voltage distribution system and it is provided effective compensation for reactive power and harmonic distortion mitigation. The simulation results are obtained using MATLAB/SIMULINK.Â Â